2013
DOI: 10.1071/wf11143
|View full text |Cite
|
Sign up to set email alerts
|

Research and development supporting risk-based wildfire effects prediction for fuels and fire management: status and needs

Abstract: Wildland fire management has moved beyond a singular focus on suppression, calling for wildfire management for ecological benefit where no critical human assets are at risk. Processes causing direct effects and indirect, long-term ecosystem changes are complex and multidimensional. Robust risk-assessment tools are required that account for highly variable effects on multiple values-at-risk and balance competing objectives, to support decision making. Providing wildland fire managers with risk-analysis tools re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 136 publications
(134 reference statements)
0
38
0
Order By: Relevance
“…Hyde et al (2013) have concluded that the current state of development in fire behaviour and effects science imposes severe limitations on the development of risk assessment analytical frameworks. The current state of risk assessment technology is a confusing array of ad hoc assessment tools that do not meet the decision support needs of fire managers.…”
Section: Risk-based Wildfire Effects Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…Hyde et al (2013) have concluded that the current state of development in fire behaviour and effects science imposes severe limitations on the development of risk assessment analytical frameworks. The current state of risk assessment technology is a confusing array of ad hoc assessment tools that do not meet the decision support needs of fire managers.…”
Section: Risk-based Wildfire Effects Managementmentioning
confidence: 99%
“…Several authors make the point that research over the past decade has applied and extended existing knowledge in many useful ways, but that significant investment in fundamental science is needed to make substantive progress on many tough issues (e.g. Finney et al 2013;Goodrick et al 2013;Hyde et al 2013). New science should be refocussed on central constructs or theories to be most effective (e.g.…”
Section: Themesmentioning
confidence: 99%
See 3 more Smart Citations